Whatsapp sebagai Media Literasi Digital Siswa - Muhammad Wildan Sahidillah; Prarasto Miftahurrisqi (Jurnal VARIDIKA, 2019)
Whatsapp is as one of the most influential social media and widely used by people in Indonesia. Students in Indonesia in the digital era are now using gadgets in their daily activities both at school and outside of school. However, most of these students use social media applications, especially Whatsapp, only for social media, whereas in the application, there are benefits that can improve digital literacy skills. The purpose of this research is to find out: 1) the use of whatsapp as the digital literacy media of students and 2) the digital literacy skills of students in terms of language skills. The method used in this study is to refer, note, and study the literature. This research is a qualitative descriptive study. The results of this study are, 1) the level of digital literacy of students with whatsapp social media is still lacking and 2) improvement of students’ digital literacy ability in terms of aspects of language ability, namely, listening, speaking, reading, watching, writing, and writing.